Design of Detection System with Motion Sensor and Notification on Android Based on Arduino Microcontroller - Rizky Ndaru Wicaksono; hindarto hindarto (Procedia of Engineering and Life Science, 2021)
The rapid development of technology nowadays makes people want to always be creative and triggers to create something that is needed to create a security system, because the difficulty of today's economy makes many people act criminally by robbery or theft. An alternative security system that is often used today is to use CCTV (Closed Circuit Television), but the limitations in conducting CCTV surveillance include that it still has to be monitored directly at the monitoring location. From the problems that occur, the authors developed a thesis that is capable of monitoring and monitoring by sending realtime alerts in the form of notifications to the user on an Android Smartphone device by building an IoT (Internet of Thing) based detection system using a PIR (Passive Infrared) motion sensor which entitled "Design of Detection System with Motion Sensor and Notification on Android Based on Arduino Microcontroller".